2009
DOI: 10.2967/jnumed.108.057372
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Embryonic Fibroblasts Treated with Platelet-Rich Plasma Induces Osteogenesis in SAMP8 Mice Monitored by Molecular Imaging

Abstract: The aim of this study was to develop a cell-based boneregeneration approach evaluated by molecular imaging and immunohistochemistry. Methods: Genetically modified NIH3T3 embryonic fibroblasts carrying enhanced green fluorescent protein (NIH3T3-G) were predifferentiated into osteoblastlike cells using platelet-rich plasma (PRP) medium, followed by intraosseous transplantation into ovariectomized senescenceaccelerated mouse prone substrain 8 (OVX-SAMP8 mice). Results: PRP-conditioned NIH3T3-G (PRP/NIH3T3-G) engr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 33 publications
2
43
0
Order By: Relevance
“…To ensure the most appropriate concentration and consistency of the purified PRP used in this study, transforming growth factor beta 1 (TGF-b1) was quantitatively analyzed using a Quantikine enzymelinked immunosorbent assay (ELISA) kit (#DB100, R&D Diagnostics, Wiesbaden, Germany) to calibrate the purified PRP concentration. Previously, results showed that a 750 pg/ml concentration of TGF-b1 in PRP was optimal for cell proliferation and differentiation [20]. Purified PRP was dissolved with alpha-minimum essential medium (alpha-MEM) media (containing 1% fetal bovine serum and 1% prostatespecific antigen) to prepare the PRP solution for use in this study.…”
Section: Prp Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure the most appropriate concentration and consistency of the purified PRP used in this study, transforming growth factor beta 1 (TGF-b1) was quantitatively analyzed using a Quantikine enzymelinked immunosorbent assay (ELISA) kit (#DB100, R&D Diagnostics, Wiesbaden, Germany) to calibrate the purified PRP concentration. Previously, results showed that a 750 pg/ml concentration of TGF-b1 in PRP was optimal for cell proliferation and differentiation [20]. Purified PRP was dissolved with alpha-minimum essential medium (alpha-MEM) media (containing 1% fetal bovine serum and 1% prostatespecific antigen) to prepare the PRP solution for use in this study.…”
Section: Prp Preparationmentioning
confidence: 99%
“…Previously, we demonstrated that platelet rich plasma (PRP) extended life span, improved survival and decreased adipogenesis in SAMP8 mice [19,20]. In this study, we hypothesized that PRP was able to delay aging through examining the characteristics of cells including cell growth (cell proliferation and colony formation), cell differentiation (osteogenesis and adipogenesis) and cellular senescence (gene, SA-b-gal activity, and oxidative stress); as well as animal morphology including life span, weight change and phenotype examination such as morphology (skin glossiness, collagen density, cataracts and lordokyphosis of the spine), bone formation and behavior (passivity and reactivity).…”
Section: Introductionmentioning
confidence: 99%
“…14). as the cells are capable of differentiating into various cell types such as neural cells, oesteocytes, and adipocytes, including insulin-producing beta cells [1,[19][20][21][24][25][26].…”
Section: In Vivo Teratoma Formation Reconfirms Pluripotency In Nih3t3mentioning
confidence: 99%
“…However, this group neither examined nor commented on the multipotent nature of these cells. Later, in 2008 and 2009, Deng and colleagues published two reports demonstrating differentiation of untransformed NIH3T3 cells into oesteocytes and neuronal cell types in bone and spinal cord injury mouse models [1,23,24]. Two other groups also reported that NIH3T3 can give rise to neural cells and oesteoblasts, respectively [21,25].…”
Section: Introductionmentioning
confidence: 99%
“…SAMP8 mice show an accelerated senescence and ageassociated pathologies such as deficits in learning and memory, brain atrophy (Takeda et al 1994). SAMP8 mice were also used to mimic senile osteoporosis (Derave et al 2005;Lo et al 2009;Wauquier et al 2012;Furuzawa et al 2014). In this light, SAMP8 mice correctly mimic aging features and pathophysiologic environment regarding senile osteoporotic establishment in humans.…”
Section: Introductionmentioning
confidence: 99%